The relevance of capital structure theories to consumer product firms at bursa Malaysia / Abdul Razak Abdul Hadi, Jaafar Pyeman and Ahmad Kasyidi Ismail. - Abdul Hadi, Abdul Razak; Pyeman, Jaafar; Ismail, Ahmad Kasyidi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2017)
This paper examines the relevance of Capital Structure Management theories to the value of consumer product firms listed at Bursa Malaysia. Within the framework of Modigliani-Miller and Trade-Off theories, this paper uses Generalized Method of Moments (GMM) as an estimation model employing yearly panel data from the year 2010 to 2014. The test results from GMM indicate that earnings per share (EPS) and debt-equity ratio (D/E) have no significant relation with the firm’s value as represented by the closing price per share (CP). Even though the findings are rather alarming, one must admit that the Modigliani-Miller and Trade-Off theories are irrelevant to those consumer product companies at Bursa Malaysia. Perhaps, this is an indication that the efficient market hypothesis applicable to certain sectors at Bursa Malaysia.